Evaluación constructiva y funcional de vivienda rural de adobe estabilizado con caña carrizo del programa nacional de vivienda rural, Huancavelica - Medina, Dedicación (2022)
The objective of this research work was to evaluate the constructive and functional state of adobe houses stabilized with reed cane from the national rural housing program, Huancavelica. The type of research that was used was applied research, the level of research was descriptive, the design was given by the non-experimental, where the general method was the scientific method, whose population and sample consisted of 20 houses built with reinforced adobe. with reed cane and non-probabilistic sampling was used for convenience, the instrument used in this investigation was the observation sheet and the technique was the observation of the dwellings under study. Concluding the research work regarding the structural state of the houses, 50% of the houses present a regular state, 30% a good state and 20% a bad state, regarding the functional state, 70% of the houses present a good state, 20% a regular state and 10% a bad system, taking into account these data, the factor that afflicts the functional system of the house is humidity, the deterioration of wood and exterior walls, due to the climatological factors of the area, and the construction process applied is given according to the specifications of the E.080 standard, said that most of the houses have a regular structural and functional state, but care must be taken and maintenance carried out necessary in order to preserve the structure of the dwelling.